Large scale synthesis of 3D nanoflowers of SnO2/TiO2 composite via electrospinning with synergistic properties - Pal, Bhupender; Zinab, H. Bakr; Krishnan, Syam G.; M. M., Yusoff; Rajan, Jose (Elsevier Ltd, 2018)
Composite of two metal oxides, SnO2 and TiO2, is synthesized as 3D nanoflowers in large quantities by electrospinning technique. They show superior energy storage properties and photocatalytic performance than their components or conventional electrospun 1D nanofibers.